White-grain Adygheiskaya corn – keeping traditions. New technologies - M. V. Kuzenko (Новые технологии, 2022)
The article shows the stages of breeding work to create a variety of white-grain Adygeiskaya corn. In order to collect, study and preserve local populations, the Institute researchers traveled to various auls and villages of Adygea. The studies were carried out in accordance with generally accepted methods of breeding work with corn. In the course of the research, the task was solved to reduce the height of plants to 2.0 m, to resist to lodging, fragility of the stem and loose smut, to increase productivity. For the period of 1999–2000 75% of the original material was rejected. In subsequent years, to increase the efficiency of selection, elite cobs were selected in the amount of 50–100 pieces after additional rejection in laboratory conditions and were sown by families. In 2007, the line AB-73 was allocated, which received the name Adygeiskaya. The new variety showed a grain yield of 60.8–71.0 centners/ha, which is 12.2 centners/ha higher than the Urvanskaya white standard, the yield of grain from the cob was 82.0%, the standard – 81.3%. Its grain is distinguished by good quality indicators: fat – 5.0%, protein – 11.9%. The variety has passed production testing in the fields of Adygea, the Krasnodar Territory and the Republic of Abkhazia. Approved for the use since 2009. High productivity and adaptability of the variety allow us to recommend it for wide use in production. The creation of the white-grain Adygeiskaya corn variety is a significant step in expanding the range of varieties used in production, as well as a contribution to the formation of a modern strategy for the scientific and technological development of the Russian Federation, the results of scientific research are important for the development of the theory and practice of breeding work.